2010
DOI: 10.1128/cvi.00369-09
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Immunological Insights on Severe, Adverse Neurotropic and Viscerotropic Disease following 17D Yellow Fever Vaccination

Abstract: Yellow fever (YF) vaccines (17D-204 and 17DD) are well tolerated and cause very low rates of severe adverse events (YEL-SAE), such as serious allergic reactions, neurotropic adverse diseases (YEL-AND), and viscerotropic diseases (YEL-AVD

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 21 publications
2
34
0
Order By: Relevance
“…A depressed monocyte cytokine synthesis was found by our group in a case with a mixed pattern of viscerotropic and neurotropic disease, in a patient with SLE. 18 Strong responses in both cell-mediated and humoral responses were found in these cases and also in a fatal case in Spain. 19 As a rule, neutralizing antibody titers are high in YEL-AVD, and taken together these findings point to defects in innate response in YEL-AVD cases.…”
Section: Vaccine-associated Viscerotropicmentioning
confidence: 98%
“…A depressed monocyte cytokine synthesis was found by our group in a case with a mixed pattern of viscerotropic and neurotropic disease, in a patient with SLE. 18 Strong responses in both cell-mediated and humoral responses were found in these cases and also in a fatal case in Spain. 19 As a rule, neutralizing antibody titers are high in YEL-AVD, and taken together these findings point to defects in innate response in YEL-AVD cases.…”
Section: Vaccine-associated Viscerotropicmentioning
confidence: 98%
“…First, ChinDENV utilizes the JE vaccine SA14-14-2, which has demonstrated an ideal safety profile in large-scale clinical usage, as the genetic backbone. Meanwhile, for YFV-17D, the backbone for CYD in clinical trials, vaccination-associated adverse events have been reported (83)(84)(85)(86)(87). Second, the Sanofi Pasteur's CYD2 vaccine carries the prM-E genes of Asian genotype I of DENV-2 (PUO-218 strain).…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of YFV-AVD is similar to severe WT YFV infection with high case-fatality rates characterized by viral replication in numerous visceral tissues and liver histopathology (Belsher et al, 2007;Centers for Disease Control and Prevention, 2002;Cetron et al, 2002;Chan et al, 2001;Gerasimon & Lowry, 2005;Martin et al, 2001;Monath et al, 2013;Vasconcelos et al, 2001). Evaluation of the immune response in a few cases of YFV-17D-associated adverse events found elevated levels of liver enzymes and cytokines similar to WT YFV infection (Bae et al, 2008;Silva et al, 2010). It has been shown that YFV-17D can infect monocytes/macrophages and endothelial cells (Goodman & Koprowski, 1962;Khaiboullina et al, 2005;Liprandi & Walder, 1983;Meier et al, 2009;Schlesinger & Brandriss, 1981), and it has been proposed that these cells are a source of dysregulated cytokine secretion leading to sepsis (Khaiboullina et al, 2005;Monath & Barrett, 2003).…”
Section: Introductionmentioning
confidence: 99%